Nonproliferative and Proliferative Lesions of the Rat and Mouse Hematolymphoid System. (August 2019) - Willard-Mack, Cynthia L.; Elmore, Susan A.; Hall, William C.; Harleman, Johannes; Kuper, C. Frieke; Losco, Patricia; Rehg, Jerold E.; Rühl-Fehlert, Christine; Ward, Jerrold M.; Weinstock, Daniel; Bradley, Alys; Hosokawa, Satoru; et al.
The INHAND Project (International Harmonization of Nomenclature and Diagnostic Criteria for Lesions in Rats and Mice) is a joint initiative of the Societies of Toxicologic Pathology from Europe (ESTP), Great Britain (BSTP), Japan (JSTP), and North America (STP) to develop an internationally accepted nomenclature for proliferative and nonproliferative changes in rats and mice. The purpose of this publication is to provide a standardized nomenclature for classifying changes observed in the hematolymphoid organs, including the bone marrow, thymus, spleen, lymph nodes, mucosa-associated lymphoid tissues, and other lymphoid tissues (serosa-associated lymphoid clusters and tertiary lymphoid structures) with color photomicrographs illustrating examples of the lesions. Sources of material included histopathology databases from government, academia, and industrial laboratories throughout the world. Content includes spontaneous lesions as well as lesions induced by exposure to test materials. The nomenclature for these organs is divided into 3 terminologies: descriptive, conventional, and enhanced. Three terms are listed for each diagnosis. The rationale for this approach and guidance for its application to toxicologic pathology are described in detail below.